1999
DOI: 10.1023/a:1007568632217
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: To physically investigate permeability upscaling over 13,000 permeability values were measured with four different sample supports (Le., sample volumes) on a block of Berea Sandstone. At each sample support spatially-exhaustive permeability data sets were measured, subject to consistent flow geometry and boundary conditions, with a specially adapted minipermeameter test system.Here, we present and analyze a subset of the data consisting of 2304 permeability values collected from a single block face oriented no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…This smoothing of the heterogeneity can be clearly verified as mentioned in previous research [16,73,74]. The block side sizes up to 1.0 m resulted in a small increase of the mean of up to 4%.…”
Section: Reproduction Of the Flow At The Coarse Scalesupporting
confidence: 87%
“…This smoothing of the heterogeneity can be clearly verified as mentioned in previous research [16,73,74]. The block side sizes up to 1.0 m resulted in a small increase of the mean of up to 4%.…”
Section: Reproduction Of the Flow At The Coarse Scalesupporting
confidence: 87%
“…A reduction of up to 83.5 % of the variance with the increasing of the block side sizes was observed. This smoothing of the heterogeneity can be clearly verified as mentioned in previous research (Hunt, 2006;Tidwell & Wilson, 1999;Vik et al, 2013b).…”
Section: Resultssupporting
confidence: 86%
“…By using particle tracking calculations, they showed that sedimentary processes are responsible for the heterogeneities that determine local groundwater flow in aquifers. The importance of connectivity on fracture flow has also been acknowledged [e.g., Journel and Alabert, 1989;Tidwell and Wilson, 1999].…”
Section: Background and Literature Reviewmentioning
confidence: 99%